(untitled) (Boletin Médico de Postgrado, 2022)
Ischemic heart disease represents the leading cause of death worldwide and Venezuela does not escape this reality. Most studies reveal a beneficial effect of cardiac rehabilitation in patients with ST elevation (STEACS) however there is little evidence in patients with non-ST elevation acute coronary syndrome (NSTEACS). This study was an observational, descriptive and retrospective design aiming to characterize the functional capacity of patients with a history of NSTEACS after the cardiovascular rehabilitation program. 55 patients with a history of NSTEACS who were admitted to the secondary prevention unit of the Centro Occidental Regional Cardiovascular Center, in the period January 2017-2020 were included. The associated pathologies in these patients were arterial hypertension (67.2%), diabetes mellitus (25.4%), overweight or obesity (14.5%), kidney disease (10.9%); the proportion of smokers and with sedentary lifestyle was 24.4% and 20%, respectively. The patients were receiving medical treatment with ACEI (30.9%), ARA II (40%), beta-blockers (90.9%), ASA (65.4%), clopidogrel (1,8%), DTAP (29%) and statins (94.5%). Patients with NSTEACS who entered the cardiac rehabilitation plan at 2 months were mostly in functional class I (94.5%). There was only one case of worsening functional class in the group of non-revascularized patients, associated with worsening angina.